Cadmium bioaccumulation and gastric bioaccessibility in cacao: A field study in areas impacted by oil activities in Ecuador. (October 2017) - Barraza, F.; Schreck, E.; Lévêque, T.; Uzu, G.; López, F.; Ruales, J.; Prunier, J.; Marquet, A.; Maurice, L.
Abstract: Cacao from South America is especially used to produce premium quality chocolate. Although the European Food Safety Authority has not established a limit for cadmium (Cd) in chocolate raw material, recent studies demonstrate that Cd concentrations in cacao beans can reach levels higher than the legal limits for dark chocolate (0.8 mg kg −1, effective January 1st, 2019). Despite the fact that the presence of Cd in agricultural soils is related to contamination by fertilizers, other potential sources must be considered in Ecuador. This field study was conducted to investigate Cd content in soils and cacao cultivated on Ecuadorian farms in areas impacted by oil activities. Soils, cacao leaves, and pod husks were collected from 31 farms in the northern Amazon and Pacific coastal regions exposed to oil production and refining and compared to two control areas. Human gastric bioaccessibility was determined in raw cacao beans and cacao liquor samples in order to assess potential health risks involved. Our results show that topsoils (0–20 cm) have higher Cd concentrations than deeper layers, exceeding the Ecuadorian legislation limit in 39% of the sampling sites. Cacao leaves accumulate more Cd than pod husks or beans but, nevertheless, 50% of the sampled beans have Cd contents above 0.8 mg kg −1 . Root-to-cacao transfer seems to be the main pathway of Cd uptake, which is not only regulated by physico-chemical soil properties but also agricultural practices. Additionally, natural Cd enrichment by volcanic inputs must not be neglected. Finally, Cd in cacao trees cannot be considered as a tracer of oil activities. Assuming that total Cd content and its bioaccessible fraction (up to 90%) in cacao beans and liquor is directly linked to those in chocolate, the health risk associated with Cd exposure varies from low to moderate. Graphical abstract: Highlights: Cd in cacao beans is enriched 4 times compared to soils contents. Cd bioaccumulates in beans mainly through root uptake regardless of soil pollution. Cd mainly originates from agricultural practices rather than oil activities. In cocoa liquor samples, Cd gastric bioaccessibility is almost 100%. 50% of cacao beans and liquor samples were above the Cd European guidelines. Abstract : This field study investigates the potential role of oil activities in Cd uptake and bioaccumulation in cacao plants in Ecuador, and proposes a health risk assessment based on Cd gastric bioaccessibility after ingestion of cacao-based products.